Defining Local Heritages in Preserving Modern Shanghai Architecture - Yongyi Lu; Yanning Li (Built Heritage, 2019)
Abstract The notion that local heritage can be defined by the ‘collective memory’ of a city may be considered as being simplistic nowadays. Heritage is increasingly recognised as knowledge, a cultural product or even a political resource set within specific social circumstances. The local heritage underpins various ways of relating our past with our present and future, which are often much more complicated than we can imagine. The evolution of the conservation of Shanghai’s modern heritage architecture shows this complexity. By tracing more than 50 years’ progress in historic preservation, this paper shows how historical buildings from Shanghai’s early modern period were selected as urban heritage in the changing socio-political contexts of different time periods. Starting with how the first modern buildings were listed in a new Chinese narrative in the 1950s, this paper focuses on the great ideological changes and progress Shanghai achieved after China’s reform and opening policy since the 1980s. Emphasising the great significance of the establishment of local legislation for historic preservation as an extension of the national system, examples of the great enrichment of Shanghai’s local heritage are presented through multiple narratives and interpretations of Shanghai’s modern history. In a deeper observation of various practices and complicated contradictions, the historic preservation of Shanghai’s modern heritage architecture is shown to be a process of continuing to reconstruct the relationships between city and the State, the city and the world, as well as the city’s past, present and future in a pluralist society.